DEVICE FOR STUDYING THE INFLUENCE OF PHYSIOLOGICAL PARAMETERS AND MICROCLIMATE ON HUMAN PRODUCTIVITY - VITALIY, BILYI; BONDARENKO, VIKTOR; BONDARENKO, NATALIIA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This article describes an innovative device for assessing the impact of physiological parameters and microclimate conditions on human productivity. The main factors affecting productivity and key parameters for monitoring are analyzed, including heart rate, blood oxygen and glucose level, body temperature, physical activity intensity, as well as air temperature, humidity, and quality. The device's structural scheme is developed using the nRF52840 microcontroller and sensors to track these parameters. The device demonstrates high energy efficiency and integration with mobile devices through Bluetooth LE. A short-term study confirms the device's potential for health and productivity monitoring.The details of configuring the device connection topology are described. It is noted that peripheral devices act as servers, providing data to central devices that function as clients. The organization and configuration of data transmission covers the use of the Attribute Protocol (ATT) and the General Attribute Profile (GATT). This structure allows efficiently configure data transfer and maintain high energy efficiency when working with different types of data. BLE wireless communication was chosen for its low energy consumption and sufficient data transfer speed (up to 2 Mbit/s with Bluetooth 5.0) to ensure the transfer of collected data to the user's mobile device or computer, where they can be displayed or analyzed using specialized applications. BLE also supports standard GATT services to simplify development and ensure compatibility with other devices. Interaction with sensors is configured via the I2C interface. The device is powered by a 2000 mAh lithium-ion battery that provides enough power to work throughout the day.
Keywords: human productivity; physiological parameters; microclimate; health monitoring; heart rate frequency; blood oxygen; glucose level; body temperature; physical activity; air quality; energy efficiency; Bluetooth LE; nRF52840 microcontroller